Lead poisoning in a 10-year-old boy with cyclic vomiting as the first symptom: a case report - Ding, Liping; Wang, Liyuan; Wang, Zhiling (Frontiers in Pediatrics, 2025)
IntroductionLead is a naturally occurring metal with highly toxic effects on humans, particularly children, who are particularly vulnerable to its long-lasting adverse impacts.Patient concernsThis report presents the case of a 10-year-old boy with a 10-month history of recurrent vomiting. No organic lesions were identified. However, the symptoms were inconsistent with cyclic vomiting syndrome (CVS), given the presence of growth retardation, vitamin D deficiency, bilateral cervical lymphadenopathy, academic difficulties, and impaired concentration.DiagnosisDetailed history-taking revealed proximity to a lead mining facility. Blood lead level (BLL) was significantly elevated (382 μg/L), confirming chronic lead poisoning.InterventionsChelation therapy with dimercaptosuccinic acid (DMSA) was administered for 19 days at a 350 mg/m2 dose per administration.OutcomesFollowing treatment, BLL decreased to 168 µg/L, accompanied by significant improvement in vomiting and abdominal pain.ConclusionPediatric lead poisoning should be considered in the differential diagnosis of children presenting with cyclic vomiting and neurological symptoms, due to its diagnostic complexity.